2015
DOI: 10.1038/jcbfm.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Amyloid Angiopathy-Related Atraumatic Convexal Subarachnoid Hemorrhage: An ARIA before the Tsunami

Abstract: Atraumatic convexal subarachnoid hemorrhage (cSAH) in elderly patients is a rare entity that has been associated with cerebral amyloid angiopathy (CAA) and intracerebral hematomas (ICH). To characterize this entity and to study these associations, 22 patients over 60 with cSAH were included in a multicenter ambispective cohort study. Clinical data, magnetic resonance imaging (MRI) studies, APOE genotyping, and cerebrospinal fluid (CSF) biomarkers were evaluated. Results were compared with data from healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 37 publications
(55 reference statements)
4
47
1
1
Order By: Relevance
“…APOE ε2 seems to be more strongly linked with cSS and bleeding, in line with a previous study on cSAH in CAA 13. This was a consistent finding in a separate cohort of CAA defined by clinicoradiographic criteria,45 as well as in a study of pathologically confirmed CAA 39.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…APOE ε2 seems to be more strongly linked with cSS and bleeding, in line with a previous study on cSAH in CAA 13. This was a consistent finding in a separate cohort of CAA defined by clinicoradiographic criteria,45 as well as in a study of pathologically confirmed CAA 39.…”
Section: Discussionsupporting
confidence: 91%
“…No studies, to the best of our knowledge, explored the whole spectrum of clinical-imaging markers of CAA in acute cSAH compared with other symptomatic CAA cases presenting without lobar ICH in the appropriate clinical context, a question of clinical relevance for accurately phenotyping the disease. Also previous studies have alluded to the potential relationship between cSAH and APOE ε2 genotype, and between cSAH and TFNEs,12 but these data are rather limited 13. Finally, the relationship from acute cSAH to cSS (ie, chronic) in a given patient has been proposed in previous reports and a recent consensus paper on the topic,8 but many aspects of this relationship have not been systematically explored at the group level and across different CAA subtypes without ICH at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, cSS, although less frequent than lobar microbleeds, was strongly associated with lobar ICH. cSS might be a particular important marker for severe CAA in AD, as it has been suggested in sporadic CAA [7]. More work in longitudinal studies is needed to confirm the higher risk conferred by cSS for future ICH and cognitive decline.…”
Section: Discussionmentioning
confidence: 98%
“…Low levels of Aβ40 and Aβ42 have been found in the CSF of subjects with sporadic CAA [7]. However, scarce and contradictory data are available about the CAA CSF biomarker profile in sporadic Alzheimer's disease patients [810], and no previous studies have assessed this profile in DS or ADAD.…”
Section: Introductionmentioning
confidence: 99%
“…4 During a median follow-up of 30.7 months, 5 patients had died, 6 survivors showed functional disability, and 12 cognitive impairment. 5 Over the same period, six patients had suffered an intracerebral hemorrhage. Compared to healthy controls, cSAH patients had an overrepresentation of the APOE ε2 allele (thought to be associated with small vessel fragility in CAA), whereas the non-cSAH CAA comparison group more often had the APOE ε4 allele.…”
mentioning
confidence: 99%